2009
DOI: 10.1523/jneurosci.3789-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Switch from Cycloheximide-Resistant Consolidated Memory to Cycloheximide-Sensitive Reconsolidation and Extinction inDrosophila

Abstract: It is generally accepted that, after learning, memories stabilize over time and integrate into long-term memory (LTM) through the process of consolidation, which depends on de novo protein synthesis. Besides, studies on several species have shown that reactivation of already stabilized LTM can either make this memory labile and then restabilize it (a process called reconsolidation) or inhibit it (extinction). However, the identity of both processes and their interactions with consolidation are still under deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
2
38
1
Order By: Relevance
“…Is it erased or hidden? Current knowledge on reconsolidation and extinction in bees [89,90] and Drosophila [91] suggests that old memories are not eliminated but only hidden by updated information. How memories are coordinated and managed requires more study.…”
Section: Experimental Evidence For a Cost Of Learning And Memory In Imentioning
confidence: 99%
“…Is it erased or hidden? Current knowledge on reconsolidation and extinction in bees [89,90] and Drosophila [91] suggests that old memories are not eliminated but only hidden by updated information. How memories are coordinated and managed requires more study.…”
Section: Experimental Evidence For a Cost Of Learning And Memory In Imentioning
confidence: 99%
“…Several studies demonstrate that the duration and the frequency of the CS presentation during memory retrieval are crucial for one of these consolidation processes to occur (Eisenberg et al, 2003;Pedreira and Maldonado, 2003;Suzuki et al, 2004;Power et al, 2006;Lagasse et al, 2009). Thus, it is critical how long and how often the previously established CS-US association is activated during retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…In these two species, as well as in some other insects (Jaffé 1980;Barraco et al 1981;Matsumoto et al 2003;Collatz et al 2006), it was shown that blocking protein synthesis impairs the consolidation of LTM (Tully et al 1994;Xia et al 1998;Menzel et al 2001;Friedrich et al 2004;Lagasse et al 2009; for review, see Schwärzel and Müller 2006). However, the extent to which LTM consolidation induces translation of the transcripts already present at the time of learning or de novo transcription followed by translation is not clear.…”
mentioning
confidence: 99%